MPS 12-07 THE INCIDENCE OF TARGET ORGAN DAMAGE AND CARDIOVASCULAR EVENTS IN TREATED HYPERTENSIVE MEN: KOREAN VETERANS HOSPITAL HYPERTENSION REGISTRY STUDY. (September 2016) - Lee, Chang Hoon; Park, Young Jun; Cho, Sang Cheol; Kim, Wan; Lee, Si Won
Abstract : Objective: The surveillance of target organ damage (TOD) and cardiovascular (CV) events is important for optimal management of subjects with hypertension. However, few studies have evaluated the incidence of TOD and CV events in Korea. The aim of study is to evaluate the incidence of TOD and CV events in hospital-based hypertensive population and association of TOD and CV events. Design and Method: From 2008 January to 2010 December, about 35, 000 Vietnam veterans were examined health for medical coverage in Korean Veterans Hospitals. Total of 6158 hypertensive men without established CV events were reviewed retrospectively using data from Korea Veterans Welfare and Healthcare Corporate. We analyzed the prevalence and incidence of TOD and CV events. Results: Mean age was 63.9 ± 3.8 years and 753 (12.5%) patients had left ventricular hypertrophy, retinopathy and nephropathy. The Kaplan-Meier survival rate was significantly higher in patients without subclinical TOD (91.2 ± 0.7 vs 82.7 ± 2.5, p < 0.001). The cumulative incidence rate of subclincal TOD, ischemic heart disease (IHD) and stroke were 10.4 ± 0.6, 20 ± 0.9 and 8.8 ± 0.6 respectively in patients (n = 5392) without TOD. The patients (n = 281) with developing TOD during follow-up had retinopathy (n = 44) and nephropathy (n = 237). The patients (n = 560) with revascularization were performed percutaneous coronary intervention (n = 498) and surgery (n = 62). The Ischemic and hemorrhagic stroke occurred in 198 (3.6%) and 56 (1.0%) patients. Conclusions: A high prevalence of 12.5% TOD in treated hypertensive men in South Korea was observed. Even treated hypertensive patients, TOD occurred 10.4% and especially IHD is high incidence of CV events. Figure. No caption available. Figure. No caption available.